Asymmetric representations of languages in contact: uses and translations of French and Spanish in Frasier - Valdeón, Roberto A. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In recent years, several authors have underlined the need for a critical approach to Translation Studies in order to explore power struggles in both source and target languages and cultures. Norman Fairclough ’s model of discourse analysis offers textual and interpretative procedures for the analy-sis of linguistic features of texts and their societal implications that can be successfully applied for this purpose. In this article we shall study the representations of languages and cultures in contact in the American situation comedy Frasier, one of the world’s greatest television successes of the 1990s. We shall cover two distinct uses of languages in contact. In our first section, we shall examine the use of other languages in the primary English discourse of the protagonists, notably French and Spanish, and their different representational and ideational implications, before proceeding to analyse the Spanish and French target versions to ascertain whether the ideological components are maintained or transformed. In the second sec-tion, we shall analyse the scenes where two or more languages are involved and the transformative acts performed by the characters. As in the first sec-tion, the target versions in French and Spanish will then be examined in order to identify the translational strategies used to maintain or tone down the ideological components. The final section will discuss the last dimension of Fairclough’s model, that is, sociocultural practice or explanation.